Kemampuan Menulis Ditinjau dari Struktur dan Bahasa Teks Narasi Siswa Kelas VII - Niken Safitri; Alber Alber (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2023)
Writing narrative texts has been taught in odd semesters at class VII SMPN 25 Pekanbaru. Writing narrative text is very important in developing students' imagination. Every student who has a different spirit of composing, students are expected to be able to develop it in the form of written narrative text or fantasy stories in accordance with KD 4.4 Presenting creative ideas in the form of fantasy stories orally and in writing taking into account the structure and use of language. This research belongs to the type of quantitative research with descriptive methods. Based on the results and discussion of research on the ability to write narrative texts for class VII students of SMP Negeri 25 Pekanbaru for the 2021/2022 Academic Year, it can be concluded that the average ability to write narrative texts for class VII students of SMP Negeri 25 Pekanbaru for the 2021/2022 Academic Year seen from the text structure = 76.3 Then the Ability to Write Narrative Texts of Class VII Students of SMP Negeri 25 Pekanbaru Judging from the Text Structure is in the Good Category; and the average ability to write narrative texts for class VII students of SMP Negeri 25 Pekanbaru for the Academic Year 2021/2022 seen from the use of language = 83.5, the ability to write narrative texts for class VII students of SMP Negeri 25 Pekanbaru seen from the use of language categories is in a good category.